A japán fürj (Coturnix japonica Temminck & Schlegel, 1849) keltetésbiológiai és testtömeg-gyarapodási vizsgálata - Vajda István (2020)
In this thesis, I examined the incubation and weight gain of Japanese quails (Coturnix japonese). The study included 303 quail eggs for incubation, and then the hatched individuals were measured by two methods; weekly measurements of the total herd as well as daily measurements of twenty randomly selected individuals were used as the basis for the calculations. The calculated data show that the average egg weight is 12 grams, which predicts more likely hatching success later on. Based on the results of weight gain, I assumed that the first two weeks are determinant of growth, so this period, as well as the feed used at that period, are critical for proper growth.